Political theory and political education (Princeton University Press, 1980)
By presenting alternative conceptions of how to link political theory to practice and education, this volume inaugurates a discussion hitherto not often attempted by modern political philosophers. Originally published in 1980. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback editions. The goal of the Princeton Legac.